Male infertility in Sertoli cell‐only syndrome: An investigation of autosomal gene defects. (26th November 2018) - Koc, Gulsah; Ozdemir, Abdullah A; Girgin, Gozde; Akbal, Cem; Kirac, Deniz; Avcilar, Tuba; Guney, Ahmet I
Abstract : Objectives: To detect autosomal genetic defects and to determine candidate genes in Sertoli cell‐only syndrome infertile men. Methods: Single‐nucleotide polymorphism + comparative genomic hybridization microarray technology was carried out on 39 Sertoli cell‐only syndrome infertile patients in the present study. Array comparative genomic hybridization compares the patient's genome against a reference genome, and identifies uncover deletions, amplifications and loss of heterozygosity. Results: A link between defective spermatogenesis genes and infertility was examined, and amplifications and deletions in several genes were detected, including homeobox gene; synaptonemal complex element protein 1; collagen, type I, alpha 1; imprinted maternally expressed transcript; and potassium voltage‐gated channel subfamily Q member 1. Conclusions: The present data suggest that several genes can play an important role in spermatogenesis and progression of Sertoli cell‐only syndrome.